Factors that influence students' motivation in choosing to study in the ppkn study program at uksw - Sa'diyah, Putri Maulinda; Mediatati, Nani (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
The purpose of this study was to determine the factors that influence students' motivation to choose to study in the PPKn study program at Satya Wacana Christian University. The method used in this study is a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. Respondents in this study were active PPKn students at the UKSW FKIP. Data validity was carried out using triangulation techniques. The data analysis technique in this study used the interactive analysis model according to Miles & Huberman which includes data collection, data reduction, data presentation, and conclusions or verification. The results of the study showed that the factors that influenced students' motivation to choose to study in the PPKn study program were internal factors such as the ideal of becoming a PPKn teacher, interests and talents. While external factors include parents, friends, community environment, and career opportunities. Students choose to study in the PPKn study program because they have certain reasons that strengthen students to choose to study in the PPKn study program. for example, students choose to study in the PPKn study program because of the great career opportunities and have been interested since school